Operation of an electric drive with a soft start device of the ssw series with smooth braking and smooth reversing - Golodnyi, I.; Toropov, A.; Sanchenko, A. (Energy and Automation, 2024)
The paper presents the algorithms of the power unit operation and voltage diagrams in the mode of economical reversal of the electric drive in the systems of adjustable asynchronous electric drive with soft starters of the SSW series. The purpose of the study is to study the operation of the power thyristor unit of the SSW6 series device during the reversal of the asynchronous motor. The analysis of instantaneous values of voltages and currents of the semiconductor power unit of the soft starter was carried out based on the provisions of the theory of electric drives, power electronics and oscillograms. A feature of asynchronous motors with a squirrel-cage rotor during direct starting is a large starting current, which is 3.5...8 times greater than the nominal one, and a starting torque, the multiplicity of which reaches 1.4...2.2. The need to limit the starting current is caused by electrical and mechanical reasons. In most cases, they try to implement control of the torque or current of the electric motor. For this purpose, using the SSW soft starter, a smooth change in voltage on the motor stator was made. These devices provide for both a controlled start and a controlled electric braking function of the electric motor, which occurs when the electric drive stops, especially when it is reversing. The required slowdown was achieved by smoothly reducing the voltage over a specified period of time. For reversing in electric drive control systems with soft starters, two external contactors are required. Digital systems on a microprocessor allow for sufficiently flexible control of the device operation process and the implementation of many additional functions and protections. Key words: soft starters, reversal, transient process, semiconductor voltage converters, voltage diagrams, electric braking of an asynchronous electric drive